2018
DOI: 10.1002/cjce.23154
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic decolourization of water using loofa sponge as cellular carrier: Immobilization and dye degradation performance

Abstract: In recent years, strong efforts have been made to develop sustainable biocatalytic decolourization processes for dye‐polluted water. In particular, dye‐oxidizing laccase enzymes immobilized on suitable carriers are promising candidates, and can be reused as long as the activity is sufficiently high. In this work, we propose, for the first time, a new methodology to immobilize laccase from Trametes hirsute on a naturally‐grown and decomposable cellular loofa sponge carrier and assess the capability to degrade d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…[ 7–10 ] It has been reported that various matrices such as synthetic, organic, and biological polymers can be used as support materials for enzyme immobilization. [ 11–17 ] Materials recommended as support in many instances are not suitable for industrial processing procedures due to their low mechanical strength, unsuitable chemical functionality, and inappropriate physical conditions. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7–10 ] It has been reported that various matrices such as synthetic, organic, and biological polymers can be used as support materials for enzyme immobilization. [ 11–17 ] Materials recommended as support in many instances are not suitable for industrial processing procedures due to their low mechanical strength, unsuitable chemical functionality, and inappropriate physical conditions. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] It has been reported that various matrices such as synthetic, organic, and biological polymers can be used as support materials for enzyme immobilization. [11][12][13][14][15][16][17] Materials recommended as support in many instances are not suitable for industrial processing procedures due to their low mechanical strength, unsuitable chemical functionality, and inappropriate physical conditions. [18][19][20][21] Three-dimensional (3-D) polymeric matrices with nano-, micro-, and macropore structures are desirable in many biomedical applications, including catalysis, drug delivery, and protection of proteins, enzymes, DNA, and other biomacromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Untreated or partially treated industrial wastewater contaminates bodies of water with toxic pollutants and these cause a serious threat to the ecosystem. The xenobiotic organic pollutants such as dyes and pigments are frequently found in the wastewater generated from dye processing industries . Since the dyes are intended to be used as colourant due to their bright colours, excellent colour fastness properties, and easy applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, decolourization tests were performed to investigate the system's ability to degrade the dye and the response surface methodology (CCS‐RSM) was applied to optimize the operation condition to a maximum dye removal. The results revealed that the loofaenzyme biocatalysis is a very efficient method for dye removal at a comparably low reaction time …”
mentioning
confidence: 99%